2014 IEEE Conference on Open Systems (ICOS) 2014
DOI: 10.1109/icos.2014.7042642
|View full text |Cite
|
Sign up to set email alerts
|

CardioOWL: An ontology-driven expert system for diagnosing coronary artery diseases

Abstract: According to World Health Organization, coronary artery diseases are responsible for 17% of the death in the world. Diagnosing the disease in the right time could lower the danger that it may cause. This paper presents an expert system (CardioOWL) that has the ability to diagnose any kind of coronary artery diseases. CardioOWL supplies the expert with the diagnosing strategies that could be used and suggests the drugs and/or other required operations to be taken. CardioOWL depends on ontology knowledge about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
6
1
Order By: Relevance
“…Other studies on the diagnosis of cardiovascular diseases based on ontologies reported an accuracy of 75.5% (10-fold cross-validation) in [8], sensitivity of 0.83 and precision of 0.87 in [7], and accuracy of more than 90% in [53].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Other studies on the diagnosis of cardiovascular diseases based on ontologies reported an accuracy of 75.5% (10-fold cross-validation) in [8], sensitivity of 0.83 and precision of 0.87 in [7], and accuracy of more than 90% in [53].…”
Section: Discussionmentioning
confidence: 96%
“…A personalized early diagnosis system based on artificial intelligence (AI), ontology, and other medical information processing systems may be a great prevention measure. Ontologies and ontology database models have been applied to the diagnosis of CVD [7,8] and other diseases such as pneumonia [9]. Ontologies are formal representations of knowledge that can be used to define the structure and content of a database, allowing the representation of complex and hierarchical relationships between different concepts [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent years, the basic technologies and techniques that have been used in disability and diseases diagnosis are Expert Systems (ES), Case-Based Reasoning (CBR), and Ontology. Expert Systems is used to support learning and decision support in diseases diagnoses [3] [4], which behave like expert human based on system knowledge and rules. Recently, different techniques and systems developed to diagnose diseases such CardioOWL Ontology-Driven ES [3], and OBESTDD Ontology-Based ES [4].…”
Section: Introductionmentioning
confidence: 99%
“…Expert Systems is used to support learning and decision support in diseases diagnoses [3] [4], which behave like expert human based on system knowledge and rules. Recently, different techniques and systems developed to diagnose diseases such CardioOWL Ontology-Driven ES [3], and OBESTDD Ontology-Based ES [4]. Case-Based Reasoning (CBR) is another effective technology in diseases diagnoses which benefits from previous problems and solutions to generate solution for the new cases.…”
Section: Introductionmentioning
confidence: 99%